Effects of Initial Performance, Gross Efficiency and O2peak Characteristics on Subsequent Adaptations to Endurance Training in Competitive Cyclists - Skovereng, Knut; Sylta, Øystein; Tønnessen, Espen; Hammarström, Daniel; Danielsen, Jørgen; Seiler, Stephen; Rønnestad, Bent R.; Sandbakk, Øyvind (Frontiers in Physiology, 2018)
The present study investigated the effects of initial levels of cycling performance, peak oxygen uptake (<inline-graphic xlink:href="fphys-09-00713-e001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />O2peak) and gross efficiency (GE) on the subsequent adaptations of these variables and their relationship following high-intensity training (HIT) designed to increase <inline-graphic xlink:href="fphys-09-00713-e001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />O2peak in competitive cyclists. Sixty cyclists (<inline-graphic xlink:href="fphys-09-00713-e001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />O2peak = 61 ± 6 mL kg-1 min-1) were assigned a 12-week training program consisting of twenty-four supervised high-intensity interval training sessions and ad libitum low intensity training. GE was calculated at 125, 175, and 225 W and performance was determined by mean power during a 40-min time-trial (Power40 min). In addition to correlation analyses between initial level and pre- to post-intervention changes of the different variables, we compared these changes between four groups where participants were categorized with either low and/or high initial levels of <inline-graphic xlink:href="fphys-09-00713-e001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />O2peak and GE. Average volume of high- and low-intensity training during the 12-week intervention was 1.5 ± 0.3 and 8.3 ± 2.7 h·week-1, respectively. Following the 12-week training period, there was a significant increase in absolute and body mass normalized <inline-graphic xlink:href="fphys-09-00713-e001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />O2peak and Power40 min (p < 0.05) and a significant decrease in GE (p < 0.05) for all athletes pooled. There was no change in body mass following the 12-week training period. We found a moderate negative correlation between initial level of <inline-graphic xlink:href="fphys-09-00713-e001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />O2peak and the change in <inline-graphic xlink:href="fphys-09-00713-e001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />O2peak following the training period (r = -0.32; p < 0.05). A small negative correlation was also found between initial Power40 min and its change following training both when expressed in absolute power and power normalized for body mass (r = -0.27 and -0.28; both p < 0.05). A moderate negative correlation was also found between initial levels for GE and its change following training (r = -0.44; p < 0.01). There were no differences between the four groups based on initial levels of <inline-graphic xlink:href="fphys-09-00713-e001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />O2peak and GE in the response to training on <inline-graphic xlink:href="fphys-09-00713-e001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />O2peak, GE, or Power40 min (all p > 0.12). In conclusion, the present findings suggest that there are statistically significant effects of initial levels of cycling performance and <inline-graphic xlink:href="fphys-09-00713-e001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />O2peak and on the subsequent adaptations following a 12-week HIT program, but the small and moderate effects indicate limited influence on training practice.